Studi Literatur: Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make a Match Terhadap Kompetensi Belajar Peserta Didik: (Literature Study: Effect of Applying Make a Match Type of Cooperative Learning on Students Learning Competencies) - Wirda Taufik; Helendra Helendra; Syamsurizal Syamsurizal; Heffi Alberida (BIODIK, 2021)
This study aims to examine the effect of the application of the make a match type of cooperative learning model on the learning competence of students. This study uses a systematic review method by reviewing several scientific articles that are relevant to the author's research. The data used in this study were obtained from scientific articles that are relevant to the problems discussed by the author. This data is taken from databases such as SINTA, Google Schoolar, and other relevant journal sites. The variables used in this study were the cooperative learning model of the make a match type (independent variable) and the learning competence of students (dependent variable). The results of this study indicate that the learning competencies (knowledge, attitudes, and skills) of students have increased after the application of the make a match type of cooperative learning model at all school levels starting from elementary, junior high, and high school. Thus, the research results are expected to strengthen and summarize the results of research related to the make a match learning model. The implications of the results of this study can be a consideration for teachers to raise the spirit of learning in students by applying the make a match learning model so that their learning competence will also increase. Abstrak. Penelitian ini bertujuan untuk mengkaji tentang pengaruh dari penerapan model pembelajaran kooperatif tipe make a match terhadap kompetensi belajar peserta didik. Penelitian ini menggunakan metode systematic review dengan mereview beberapa artikel ilmiah yang relevan dengan penelitian penulis. Data yang digunakan dalam penelitian ini diperoleh dari artikel ilmiah yang relevan dengan permasalahan yang dibahas oleh penulis. Data ini diambil dari database seperti SINTA, Google Schoolar, dan situs jurnal lainnya yang relevan. Variabel yang digunakan dalam penelitian ini adalah model pembelajaran kooperatif tipe make a match (variabel bebas) dan kompetensi belajar peserta didik (variabel terikat). Hasil penelitian ini menunjukkan bahwa kompetensi belajar (pengetahuan, sikap, dan keterampilan) peserta didik mengalami peningkatan setelah penerapan model pembelajaran kooperatif tipe make a match di semua tingkatan sekolah mulai dari SD, SMP, dan SMA. Jadi model pembelajaran kooperatif tipe make a match ini memberikan pengaruh yang positif terhadap kompetensi belajar peserta didik. Dengan demikian, model pembelajaran make a match ini bisa menjadi pertimbangan oleh guruÂ  untuk membangkitkan kembali semangat belajar peserta didik sehingga kompetensi belajarnya juga akan meningkat.